Transoral endoscopic coblation adenoidectomy - a novel approach of performing adenoidectomy in children - John, Nikhil M.; Ashok, Vivekananda; Varghese, Tija S. (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2024)
Background: Adenoidectomy stands as one of the most frequently performed surgical procedures in children. Coblation adenoidectomy has emerged as a preferred method, with advantages such as diminished postoperative pain and swifter recovery. However, its application via trans nasal access in children, particularly those with anatomical variations, poses significant challenges. The aim of this study is to introduce and evaluate the advantages and limitations of transoral endoscopic coblation adenoidectomy in paediatric patients, with a focus on assessing its efficacy and safety. Methods: A total of 80 children who presented to the outpatient department with chronic adenoid hypertrophy, aged between 2 and 12 years, were selected for participation in this study. Transoral coblation adenoidectomy was performed on all selected patients. The procedure was carried out with the patient placed in either Rose position or reverse Trendelenburg position, chosen randomly. Results: Complete clearance of adenoid tissue was done under visualisation. There were no intraoperative adverse events. Bleeding during the procedure was minimal, suggesting excellent hemostasis. Postoperative pain reported by patients were minimal. Conclusions: Transoral endoscopic coblation adenoidectomy stands as a promising approach in the management of chronic adenoid hypertrophy in children, offering more advantages in children with narrow airways and coexisting anatomical variations. The findings of this study support the notion that transoral endoscopic coblation adenoidectomy achieves complete clearance of adenoid tissue with minimal intraoperative adverse events and postoperative complications. Additionally, the procedure results in minimal postoperative pain and allows for shorter hospital stay.